Cola rostrata K. Schum. constituents induce cytotoxicity through reactive oxygen species generation and mitochondrial membrane depolarisation - Babatunde E. Ajayi; Bola Oboh; Joseph B. Minari; Darren W. Sexton; Satyajit D. Sarker; Amos A. Fatokun (Exploration of Targeted Anti-tumor Therapy, 2023)
Aim: While the traditional use of Cola rostrata in treating illnesses and diseases has not been reported, the presence of cytotoxic principles has been reported in phylogenetically and biogeographically related species within the Cola genus. This study, therefore, evaluated the cytotoxic potential of extracts of the plant, and the associated cellular and molecular mechanisms. Methods: Activity-based fractionation of the extracts was carried out and cytotoxicity was assessed in the human cervical cancer cell line, HeLa, and the transformed human lung cell line, MRC5-SV2, using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay complemented with brightfield imaging. The 2ʼ,7ʼ-dichlorofluorescein diacetate (DCFDA) assay was used to assess induction of cellular reactive oxygen species (ROS), while flow cytometry of 5,5ʼ,6,6ʼ-tetrachloro-1,1ʼ,3,3ʼ-tetraethyl-imidacarbocyanine iodide (JC-1)-stained cells assessed the loss of mitochondrial membrane potential (∆ΨM). Gas chromatography-mass spectrometry (GC-MS) analysis was carried out on an active fraction. Results: Extracts of the fruit epicarp and leaf were cytotoxic against the cell lines. Half-maximal inhibitory concentration (IC50) values for the 48 h cytotoxicity of the ethanol extract of the epicarp against HeLa and MRC5-SV2 cells were 48.0 μg/mL ± 12.1 μg/mL and 40.4 μg/mL ± 7.2 μg/mL, respectively, while fractions from second-level partitioning of the hexane fraction of the leaf extract elicited cytotoxicity with IC50 values ranging from 12.8 μg/mL ± 1.0 μg/mL to 39.6 μg/mL ± 7.2 μg/mL in both cell lines, following 48 h treatment. GC-MS revealed the presence of seventeen compounds in a hexane fraction of the leaf extract, including even- and odd-chain fatty acids, the most abundant of which were n-hexadecanoic acid, decanoic acid 10-(2-hexylcyclopropyl); and octadecanoic acid. The mechanisms of cytotoxicity of most active fractions involved generation of ROS and mitochondrial membrane depolarisation. Conclusions: The findings show that C. rostrata is rich in cytotoxic phytochemicals which could be isolated for developing new anti-cancer agents.